2016
DOI: 10.1308/rcsann.2016.0254
|View full text |Cite
|
Sign up to set email alerts
|

Choosing between the modified Ravitch and Nuss procedures for pectus excavatum: Considering the patients’s perspective

Abstract: INTRODUCTION Pectus excavatum (PE) is the most common paediatric chest wall deformity. The majority of patients are treated for cosmetic purposes, with the modified Ravitch and Nuss procedures the most commonly performed. We tested the preferences of healthy individuals over their choice of procedure. METHODS The study was conducted from February to August 2014. A five-item illustrated questionnaire was administered to teenagers and young adults aged 14-26 years over their willingness to seek medical advice if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…The EBL within our study had a median of 110 mL, which falls within the wide range of other reports of 33 mL to 359 mL with similar repairs. 10 , 11 The median LOS among our cohort was 4 days, which is comparable with other reports. 11 The shorter operative times in our study while maintaining acceptable EBL and LOS suggest that our method remains an efficient procedure.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The EBL within our study had a median of 110 mL, which falls within the wide range of other reports of 33 mL to 359 mL with similar repairs. 10 , 11 The median LOS among our cohort was 4 days, which is comparable with other reports. 11 The shorter operative times in our study while maintaining acceptable EBL and LOS suggest that our method remains an efficient procedure.…”
Section: Discussionsupporting
confidence: 90%
“…Multiple studies have compared open and minimally invasive techniques to understand the relative success associated with each method. 3 , 6 , 10 , 11 Perioperative data show similar findings in operative times, estimated blood loss (EBL), and postoperative length of stay (LOS). 6 , 10 Although the minimally invasive approach of the Nuss procedure offers several advantages, the Ravitch type repair has been shown to have a higher degree of long-term satisfaction.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“… 24 Patient preference should be considered however, as recent studies have also suggested that many patients have strong preferences regarding whether they would prefer a minimally invasive procedure or whether they would prefer not to have metalwork in their body. 32 …”
Section: Pectus Excavatummentioning
confidence: 99%
“…The Nuss procedure is a minimally invasive alternative to the Ravitch procedure for the treatment of pectus deformities. It involves only internal bracing without resection of the abnormal cartilage [8]. It aims to force the sternum forward and hold it there with an implanted steel bar, but without performing a long incision to resect the abnormal cartilage [5].…”
Section: Ravitch Proposed the First Technique Of Pectus Excavatum Repmentioning
confidence: 99%